Validating reduced models for detachment onset and reattachment times on MAST-U - S.S. Henderson; M. Bernert; D. Brida; G.L. Derks; S. Elmore; F. Federici; J.R. Harrison; A. Kirk; B. Kool; N. Lonigro; J. Lovell; D. Moulton; et al. (Nuclear Materials and Energy)
Two reduced models for predicting detachment onset and divertor reattachment times are validated on MAST Upgrade (MAST-U). These models are essential for future tokamak reactor design, providing rapid calculations based primarily on engineering parameters. The first model predicts detachment onset using a qualifier developed on ASDEX Upgrade (AUG) and later tested on JET, while the second model provides an estimate for the time required for a given transient to burn through the neutral particles in the divertor. Experiments in H-mode plasma scenarios were conducted on MAST-U with double-null and single-null configurations, which involved D2 fuelling ramps and N2 seeding. The detachment onset was determined by monitoring divertor parameters, including the target heat flux profile, electron temperature, and electron density, with measurements showing consistency with AUG-derived predictions. Reattachment times were assessed during dynamic vertical shifts of the plasma centroid position, with observations indicating reattachment within milliseconds, consistent with model predictions. Overall, the results confirm the applicability of both reduced models to MAST-U, extending their validation beyond AUG and JET.